Structure-activity relationship study of the pyridine moiety of isothiazolo[4, 3-b]pyridines as antiviral agents targeting cyclin G-associated kinase. Issue 1 (1st January 2020) - Martinez-Gualda, Belén; Pu, Szu-Yuan; Froeyen, Mathy; Herdewijn, Piet; Einav, Shirit; De Jonghe, Steven
Graphical abstract: Highlights: Novel 3, 5- and 3, 6-disubstituted isothiazolo[4, 3- b ]pyridines were synthesized. Compounds were evaluated for GAK binding affinity. The most potent isothiazolo[4, 3- b ]pyridine analogue was endowed with a GAK IC50 value of 0.024 µM. This compound also exhibited antiviral activity against dengue virus. Abstract: Previously, we reported the discovery of 3, 6-disubstituted isothiazolo[4, 3- b ]pyridines as potent and selective cyclin G-associated kinase (GAK) inhibitors with promising antiviral activity. In this manuscript, the structure-activity relationship study was expanded to synthesis of isothiazolo[4, 3- b ]pyridines with modifications of the pyridine moiety. This effort led to the discovery of an isothiazolo[4, 3- b ]pyridine derivative with a 3, 4-dimethoxyphenyl residue at position 5 that displayed low nanomolar GAK binding affinity and antiviral activity against dengue virus.